Functional changes of immune cells: signal of immune tolerance of the ectopic lesions in endometriosis?. Issue 2 (August 2021) - Voltolini Velho, Renata; Halben, Nicolette; Chekerov, Radoslav; Keye, Jacqueline; Plendl, Johanna; Sehouli, Jalid; Mechsner, Sylvia
HIGHLIGHTS: Immune cells frequencies were not different between controls and EM patients 13 cytokines were increased in EM patients Correlations between IL-2, MCP-1, MIP-1α, TNF-α and EM severity were noted The concentration of neopterin in EM patients was increased compared to controls Changing activities of cytokine profile (TH 1 to TH 2) have a beneficial effect on EM Abstract: Research question: What is the potential role of immune cells and their inflammatory cytokines in the pathogenesis, development and establishment of endometriosis? Design: Peritoneal fluid from 59 women (43 with endometriosis and 16 controls) who had undergone laparoscopic surgery was analysed. Changes in the population of innate and adaptive immune cells, cytokines, chemokines and growth factor expression were measured by flow cytometry, Luminex Technology and enzyme-linked immunosorbent assay. Results: No differences were found in the frequencies of the innate and adaptive immune cells between women with and without endometriosis. In the peritoneal fluid of women with endometriosis, IL-1β, IL-1RN, IL-2, IL-4, IL-8, IL-10, IL-12 (p70), IL-17α, FGF2, G-CSF, MCP-1, MIP-1α and TNF-α were significantly increased compared with controls. A correlation between IL-2, MCP-1, MIP-1α, TNF-α and the severity of endometriosis was observed. The concentration of neopterin, a possible biomarker for this disease, was increased in women with endometriosis compared with controls. Conclusions: The functional activity of immune cells seemed to be reduced despite their numbers remaining unchanged. The data indicate that a shift of TH cytokine profile occurs, which increases the TH 1–TH 2 ratio. This is driven by the increased levels of the cytokines (TNF-α and IL-2) in women with severe endometriosis.